Distinct Phenotypes of Inflammation Associated Macrophages and Microglia in the Prefrontal Cortex Schizophrenia Compared to Controls - Zhu, Yunting; Webster, Maree J.; Murphy, Caitlin E.; Middleton, Frank A.; Massa, Paul T.; Liu, Chunyu; Dai, Rujia; Weickert, Cyndi Shannon (Frontiers in Neuroscience, 2022)
Approximately 40% of people with schizophrenia are classified as having ‘high inflammation’. This subgroup has worse neuropathology than patients with ‘low inflammation’. Thus, one would expect the resident microglia and possibly monocyte-derived macrophages infiltrating from the periphery to be “activated” in those with schizophrenia with elevated neuroinflammation. To test whether microglia and/or macrophages are associated with increased inflammatory signaling in schizophrenia, we measured microglia- and macrophage-associated transcripts in the postmortem dorsolateral prefrontal cortex of 69 controls and 72 people with schizophrenia. Both groups were stratified by neuroinflammatory status based on cortical mRNA levels of cytokines and SERPINA3. We found microglial mRNAs levels were either unchanged (IBA1 and Hexb, p>0.20) or decreased (CD11c, <62% p<0.001) in high inflammation schizophrenia compared to controls. Conversely, macrophage CD163 mRNA levels were increased in patients, substantially so in the high inflammation schizophrenia subgroup compared to low inflammation subgroup (>250%, p<0.0001). In contrast, high inflammation controls did not have elevated CD163 mRNA compared to low inflammation controls (p>0.05). The pro-inflammatory macrophage marker (CD64 mRNA) was elevated (>160%, all p<0.05) and more related to CD163 mRNA in the high inflammation schizophrenia subgroup compared to high inflammation controls, while anti-inflammatory macrophage and cytokine markers (CD206 and IL-10 mRNAs) were either unchanged or decreased in schizophrenia. Finally, macrophage recruitment chemokine CCL2 mRNA was increased in schizophrenia (>200%, p<0.0001) and CCL2 mRNA levels positively correlated with CD163 mRNA (r=0.46, p<0.0001). Collectively, our findings support the co-existence of quiescent microglia and increased pro-inflammatory macrophages in the cortex of people with schizophrenia.